Green Sukuk: Tantangan dan Strategi Pengembangan Untuk Pembangunan Berkelanjutan Serta Menuju Ekonomi Hijau - Arifudin Arifudin; Neli Anjani; Neneng Serliana; Mia Auliah; Amaliah Amaliah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Green Sukuk is a financial instrument that combines the principles of Islamic finance with sustainable development goals. This article discusses the role, practices, mechanisms, as well as challenges and efforts of the government in developing Green Sukuk in Indonesia. Green Sukuk have great potential in supporting the transition to a sustainable economy by providing a source of funding for environmentally friendly projects. However, challenges such as lack of awareness and capacity of financial institutions need to be overcome to optimize the contribution of Green Sukuk. Through strengthening regulations, outreach, product innovation and international cooperation, it is hoped that the Green Sukuk market can continue to develop and support the achievement of sustainable development goals in Indonesia.